Using the Instagram Reels Feature @aryusaraah as a Medium for Self-Presentation - Nina Amelia; Aghnia Dian Lestari (Journal of Social Research, 2026)
Instagram Reels, which are used as a medium for sharing daily life, have led to the emergence of mom influencers who use social media as a space for self-image formation. This study aims to analyze the self-presentation strategies of the Instagram account @aryusaraah through Reels by examining the management of the front stage and backstage, as well as understanding the motivation for using Reels as a means of self-image formation. This study uses Erving Goffman's dramaturgy theory to understand role management and the boundaries between private and public spaces. The method used is descriptive qualitative with data collection techniques in the form of interviews with account owners and active followers, as well as observation of Reels content. The results show that @aryusaraah consistently manages her personal front stage through adjustments to content themes, expressions, settings, appearances, and interaction patterns. The front stage presents the image of a young mother who is active in her activities while still taking care of her children, while the back stage is evident in the curation process and the restriction of personal aspects that are not in line with the image being built. The motivation to produce Reels is driven by the desire to share experiences, express oneself, and receive responses from followers. Through her Reels posts, Aryu Sarah successfully presents herself in line with the image she has built, without straying far from her real life.